Lateral bending behavior and calculation of perforated cross-plate joints in lattice-shaped diaphragm walls - Li, Ke; Yang, Rui; Tu, Weicheng; Hu, Qinxin; Kong, Qian (Frontiers in Earth Science, 2025)
IntroductionLattice-shaped diaphragm walls (LSDWs) are increasingly used in bridge foundations and foundation pit enclosures due to their high vertical and horizontal load-bearing capacity. Unlike conventional diaphragm walls that mainly support vertical loads, LSDWs are predominantly subjected to horizontal forces during excavation. However, the lateral bending behavior of their joints—particularly perforated cross-plate joints (PCPJs)—remains insufficiently studied. This paper aims to investigate the lateral bending performance of single- and double-cross PCPJs, a critical joint type in LSDWs.MethodsAn experimental program was conducted involving eight sets of PCPJ specimens and one non-jointed wall segment. Four-point bending tests were carried out to analyze the influence of the steel plate perforation ratio on the load–displacement response and ultimate bearing capacity. Typical failure modes and mechanisms were identified, and a calculation method for the lateral bending capacity of PCPJs was proposed.ResultsThe lateral bending failure of PCPJs was characterized by separation at the web–lower flange steel–concrete interface, fracture of the concrete dowel, and tensile cracking at the end of the steel plate flange. The bending capacities during the elastic stage reached 25.5% and 44.9% of the ultimate load for single- and double-cross PCPJs, respectively. The double-cross PCPJ exhibited higher lateral bending capacity than the single-cross type—approximately 1.6 times under the same perforation ratio—though still lower than the non-jointed segment. Additionally, lateral bearing capacity correlated positively with perforation ratio, with double-cross joints showing greater sensitivity to this parameter.DiscussionThe proposed calculation method for lateral bending capacity showed good agreement with experimental values, with deviations ranging from −2.16% to 6.20%, demonstrating its reliability. These findings provide important insights into the structural performance of PCPJs and offer a valuable reference for the design and application of LSDWs in similar engineering applications.